Correction to: Reef refugia in the aftermath of past episodes of global warming (Coral Reefs, (2024), 43, 5, (1431-1442), 10.1007/s00338-024-02548-y) - Dimitrijevic, Danijela; Santodomingo, Nadia; Kießling, Wolfgang (Coral Reefs, 2024)
The original article has been corrected. In Fig. 2, the y-axis names were inadvertently inverted during proofing. In Fig. 2.a, the y-axis was published as "0–50–100–150" and should have been "0–20–40–60–80–100". In Fig. 2.b, the y-axis was published as "0–20–40–60–80–100" and should have been "0–50–100–150".
CRIS-Team Scopus Importer:2024-10-18